Vestibular rehabilitation in Europe: a survey of clinical and research practice - Meldrum, Dara; Burrows, Lisa; Cakrt, Ondrej; Kerkeni, Hassen; Lopez, Christophe; Tjernstrom, Frederik; Vereeck, Luc; Zur, Oz; Jahn, Klaus (Journal of neurology, 2020)
Vestibular rehabilitation (VR) is practiced across Europe but little in this area has been quantified. The aim of this study was to investigate current VR assessment, treatment, education, and research practices. This was an online, cross-sectional survey with 39 VR specific questions and four sections: demographics, current practice, education, and research. The survey was disseminated through the Dizzynet network to individual therapists through country-specific VR special interest groups. Results were analysed descriptively. A thematic approach was taken to analyse open questions. A total of 471 individuals (median age 41, range 23 - 68 years, 73.4% women), predominately physiotherapists (89.4%) from 20 European countries responded to the survey. They had worked for a median of 4 years (range < 1 - 35) in VR. The majority (58.7%) worked in hospital in-patient or out-patient settings and 21.4% in dedicated VR services. Most respondents specialized in neurology, care of the elderly (geriatrics), or otorhinolaryngology. VR was reported as hard/very hard to access by 48%, with the main barriers to access identified as lack of knowledge of health care professionals (particularly family physicians), lack of trained therapists, and lack of local services. Most respondents reported to know and treat benign paroxysmal positional vertigo (BPPV 87.5%), unilateral vestibular hypofunction (75.6%), and cervicogenic dizziness (63%). The use of vestibular assessment equipment varied widely. Over 70% used high-density foam and objective gait speed testing. Over 50% used dynamic visual acuity equipment. Infrared systems, Frenzel lenses, and dynamic posturography were not commonly employed (< 20%). The most frequently used physical outcome measures were the Clinical Test of the Sensory Interaction of Balance, Functional Gait Assessment/Dynamic Gait Index, and Romberg/Tandem Romberg. The Dizziness Handicap Inventory, Visual Analogue Scale, Falls Efficacy Scale, and the Vertigo Symptom Scale were the most commonly used patient reported outcome measures. Adaptation, balance, and habituation exercises were most frequently used (> 80%), with virtual reality used by 15.6%. Over 70% reported knowledge/use of Semont, Epley and Barbeque-Roll manoeuvres for the treatment of BPPV. Most education regarding VR was obtained at post-registration level (89.5%) with only 19% reporting pre-registration education. There was strong (78%) agreement that therapists should have professionally accredited postgraduate certification in VR, with blended learning the most popular mode. Three major research questions were identified for priority: management of specific conditions, effectiveness of VR, and mechanisms/factors influencing vestibular compensation and VR. In summary, the survey quantified current clinical practice in VR across Europe. Knowledge and treatment of common vestibular diseases was high, but use of published subjective and objective outcome measures as well as vestibular assessment varied widely. The results stress the need of improving both training of therapists and standards of care. A European approach, taking advantage of best practices in some countries, seems a reasonable approach.
Keywords: senioři; Dizziness; Cross-Sectional Studies; závrať; Europe; Benign paroxysmal positional vertigo; Evropa; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Vestibular education; průřezové studie; Adult; mladý dospělý; Vestibular assessment; Young Adult; ženské pohlaví; Humans; Surveys and Questionnaires; Vestibular rehabilitation; lidé středního věku; vestibulární nemoci; dospělí; Vestibular Diseases; Female; Aged; Vertigo; lidé; Male